Plant organ abscission and the green island effect caused by a coleopteran’s gall on Miconia cf cinnamomifolia (Melastomataceae): larval survival and mortality factors - Santos, Jean Carlos; Miranda, Rodrigo de Queiroga; Almeida-Cortez, Jarcilene Silva de (Journal of Environmental Analysis and Progress, 2017)
Galls are characterized by inducing cellular differentiation (hyperplasia or hypertrophy) resultant of the action of some organisms, mainly insects, on structures/organs of their host plants. The galls cause physiological changes in host plants, altering host traits, and their growth and survival. The early abscission of galled plant organs can be a form of plant defense. Therefore, the galls decayed more slowly than the healthy leaves, or the surrounding healthy leaf tissue in some abscised galled leaves, forming “green island galls”. This study reported an instance where the host plant Miconia cinnamomifolia (Melastomataceae) abscises leaves galled by an unidentified coleopteran’s gall on the soil of a fragment of Atlantic Forests, Brazil. Once on the forest soil galls were exposed to a new set of potential natural enemies, as pathogens and predators. Consequently, larval survival decrease of 79% to 36% in four months and fungal infestation increase of 2% to 21%. Neither size nor weight of the galls differed between categories of mortality factors and larval survival. It was discussed the adaptive nature of the “Green Island Effect” as a counter-response of gallers to leaf abscission, which is a known plant defense strategy.